Inverted ILM Flap Technique - Jerzy Nawrocki, Zofia Michalewska (Pakistan Journal of Ophthalmology, 2019)
As recently as 30 years ago, macular holes were thought to be untreatable. Kelly and Wendel showed that this was not the case in 1991 when they published their pilot study on vitreous surgery for idiopathic macular holes1. In 1997, Eckardt et al. introduced internal limiting membrane (ILM) peeling2, following which, pars plana vitrectomy, internal limiting membrane peeling, fluid/gas exchange and face-down positioning were soon adopted as the standard treatment method for successful hole closure and BCVA improvement. Surgeons improved their own results by using smaller gauge instruments and, especially, by more qualified patient selection: earlier treatment, non-myopic eyes, better initial visual acuity, and smaller macular holes.